2019
DOI: 10.1002/cjp2.140
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the endocrine pancreas in type 1 diabetes: islet size is maintained but islet number is markedly reduced

Abstract: Insulin deficiency in type 1 diabetes (T1D) is generally considered a consequence of immune-mediated specific beta-cell loss. Since healthy pancreatic islets consist of~65% beta cells, this would lead to reduced islet size, while the number of islets per pancreas volume (islet density) would not be affected. In this study, we compared the islet density, size, and size distribution in biopsies from subjects with recent-onset or long-standing T1D, with that in matched non-diabetic subjects. The results presented… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 30 publications
(40 reference statements)
1
30
1
Order By: Relevance
“…Recently, the Kushner laboratory has provided evidence that some of the remaining insulin in the blood stream of patients with long-term T1D 57 originates from dedifferentiated β cells and/or from polyhormonal non-β cells that function as 'insulin microsecretors' 58 . Similarly, the Korsgren laboratory found histological evidence for β-cell dedifferentiation at T1D onset 59 . Therefore, triggering the redifferentiation of dedifferentiated β cells seems to be an intuitive approach for the treatment of diabetes that does not involve β-cell proliferation or neogenesis per se 60 .…”
Section: Discussionmentioning
confidence: 85%
“…Recently, the Kushner laboratory has provided evidence that some of the remaining insulin in the blood stream of patients with long-term T1D 57 originates from dedifferentiated β cells and/or from polyhormonal non-β cells that function as 'insulin microsecretors' 58 . Similarly, the Korsgren laboratory found histological evidence for β-cell dedifferentiation at T1D onset 59 . Therefore, triggering the redifferentiation of dedifferentiated β cells seems to be an intuitive approach for the treatment of diabetes that does not involve β-cell proliferation or neogenesis per se 60 .…”
Section: Discussionmentioning
confidence: 85%
“…In accordance with the abovementioned work, another study showed the existence of PDX1-expressing α-cells (glucagon positive cells) in biopsies from patients with T1D. The authors speculated that these are exhausted β-cells, transdifferentiated towards the α-cell fate under extreme conditions [151]. These changes in identity might hide the cells from the immune system and prevent the onset or progression of the disease, as shown in another study in which by inducing proliferation and thus maintaining the immature features of β-cells, it was possible to prevent the progression of T1D in NOD mice [152].…”
Section: Diabetic Conditions: β-Cells Derailmentioning
confidence: 59%
“…However, surprisingly, the CD3 + immune infiltrate was not localized to the smaller islets or within a particular islet region (16). In humans, individuals with recent-onset type 1 diabetes have larger islets compared with people with long standing type 1 diabetes (17).…”
Section: Discussionmentioning
confidence: 91%